A Dual‐Responsive Luminescent Terbium(III) Chain for Selective Sensing of Fe3+ and MnO4– Ions. Issue 23 (26th September 2018) - Shi, Jia‐Li; Xu, Ping; Wang, Xiu‐Guang; Ding, Bo; Zhao, Xiao‐Jun; Yang, En‐Cui
Abstract : A new one‐dimensional double chain with two symmetry‐related Tb 3+ ions extended by pairs of butanedioate connectors, {[Tb(H2 O)(L)(TPA)]· 0.5H2 O} n [TPA = 6‐(1H‐1, 2, 4‐triazol‐1‐yl)pyridine‐2‐carboxylate and L = butanedioate] was solvothermally prepared by popular mixed‐ligand strategy. Possessing highly thermal and environmental stability, the complex exhibits bright green emission in well‐dispersed water system, and can efficiently detect Fe 3+ and MnO4 – ions through fluorescence quenching with strong quench constants ( K sv = 8.51 × 10 3 and 1.13 × 10 4 m – 1 ) and low limits of detection (2.29 and 1.43 μm ). These interesting results indicate that low‐dimensional coordination polymers can be promisingly used as dual‐functional luminescent sensors for detecting the environmental pollutants. Abstract :